Philological Analysis of the Sundanese Folklore ’Lutung Kasarungâ€™ - Subandiyah, Heny; Supratno, Haris; Permata, Resdianto; Fahri, Fahri; Abida, Fithriyah Inda Nur (JOLLT Journal of Languages and Language Teaching, 2023)
One of the most well-known and beloved Sundanese folklore stories is the "Lutung Kasarung" tale, which has been adapted and retold in various forms across the region. Therefore, this study aims to analyze the Sundanese folklore "Lutung Kasarung" from a philological perspective. The main objective of this study is to investigate how the Sundanese language is employed to reflect the values, traditions, and culture of the Sundanese community, and evaluating its contribution to the preservation of the Sundanese cultural heritage. The study employs qualitative methodology, using library research and interviews as research instruments. The findings of the research indicate that the use of language in the "Lutung Kasarung" folklore includes various linguistic elements, including ’Undak Usuk Basa’, figurative language, poetic verses (pantun), and vocabulary or phrases associated with cultural expressions. The study’s findings also highlight the significance of values such as honesty, loyalty, and kindness, as well as the repercussions of greed and selfishness, which are greatly emphasized in Sundanese cultural traditions. A key contribution of this research is its commitment to preserving the Sundanese language and culture. By meticulously examining how Sundanese is used in the folklore, it not only safeguards the language but also ensures that cultural elements embedded within it are recognized and celebrated.Â